2011
DOI: 10.1074/jbc.m111.255224
|View full text |Cite
|
Sign up to set email alerts
|

Expanded CUG Repeats Dysregulate RNA Splicing by Altering the Stoichiometry of the Muscleblind 1 Complex

Abstract: To understand the role of the splice regulator muscleblind 1 (MBNL1) in the development of RNA splice defects in myotonic dystrophy I (DM1), we purified RNA-independent MBNL1 complexes from normal human myoblasts and examined the behavior of these complexes in DM1 myoblasts. Antibodies recognizing MBNL1 variants (MBNL1 CUG ), which can sequester in the toxic CUG RNA foci that develop in DM1 nuclei, were used to purify MBNL1 CUG complexes from normal myoblasts. In normal myoblasts, MBNL1 CUG bind 10 proteins in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 37 publications
2
63
0
Order By: Relevance
“…However, in higher eukaryotes, alternative splicing expands the complexity of the proteome in different tissues (56,57), and this is achieved through complex networks of protein-RNA interactions (58 -60). All three ARVCF-interacting proteins were reported to be involved in alternative splicing of specific genes (37,45,59,61). Upon knockdown of ARVCF, alternative splicing of several genes was significantly altered in our study.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…However, in higher eukaryotes, alternative splicing expands the complexity of the proteome in different tissues (56,57), and this is achieved through complex networks of protein-RNA interactions (58 -60). All three ARVCF-interacting proteins were reported to be involved in alternative splicing of specific genes (37,45,59,61). Upon knockdown of ARVCF, alternative splicing of several genes was significantly altered in our study.…”
Section: Discussionmentioning
confidence: 50%
“…Aberrant RNA processing by alternative splicing of genes related to schizophrenia had been frequently observed in the past (69,70), and this was correlated with the pathophysiology of the disorder. In future studies, it will be clarified whether ARVCF contributes to malfunctions in alternative splicing that may lead to aberrant pre-mRNA splicing events giving rise to neurological disorders, such as schizophrenia, or other human diseases, such as myotonic dystrophy or cancer (33,61,71,72).…”
Section: Discussionmentioning
confidence: 99%
“…Recent analysis of the proteins bound to CUG repeats showed that p68 binds to CUG foci and modulates splicing activity of MBNL1 (14). It appears that p68 levels are increased in immortalized cultured DM1 myoblasts (17). However, p68 levels were reduced in DM1 biopsied muscle (Fig.…”
Section: Resultsmentioning
confidence: 81%
“…HnRNP H protein levels are also elevated in DM1 myoblasts and hnRNP H or CELF1 overexpression leads to the formation of a repressor complex that inhibits splicing of insulin receptor (IR) exon 11 (Paul et al, 2006). HnRNP H exists in a complex with MBNL1 and 9 other proteins (hnRNP H2, H3, F, A2/B1, K, L, DDX5, DDX17, and DHX9) in normal myoblast extracts but the stoichiometry of these complexes is altered in DM1 extracts (Paul et al, 2011). Staufen1 (STAU1) is a double-stranded (ds)RNA-binding protein that is also mis-regulated in DM1 skeletal muscle (Ravel-Chapuis et al, 2012).…”
Section: 2 Rna Toxicity and Protein Sequestration In Myotonic Dystrmentioning
confidence: 99%